Performance assessment of mobile computation offloading - Seifaddini, Omid; Abdullah, Azizol; Hussin, Masnida; Muhammed, Abdullah (IEEE (IEEE Xplore), 2014)
Offloading is a technique that resource poor mobile devices try to alleviate the resource constrained by migrating partial or full heavy computation part of mobile application to the more resourceful platforms such as cloud computing. This paper presents an analysis and overview of cloud based mobile computation offloading performance based on the current Internet infrastructure and backbone in Malaysia specifically in Peninsular Malaysia, Serdang area. The experimental results show that the current developing infrastructure and backbone need to be more enhanced in order to support mobile offloading.